Koncepcja narodu w myśli Floriana Znanieckiego: próba interpretacji - Brzechczyn, Krzysztof (My University, 2024)
The purpose of the paper is reconstruction of Florian Znaniecki's theory of the nation. The basis of my interpretation will be following questions or research problems: (i) Does national membership result from the possession of certain features, or is it a question of free will? (ii) Were nation-building processes autonomous with regards to socio-political and socio-economical processes, or were they reducible to them? (iii) Did one universal path of nation-building exist (at least in Europe) or were there more paths? The answer to these questions allows Znaniecki's theory to be located in a wider comparative perspective, from which his opinions can be compared with those of other authors (such as e.g. Zygmunt Balicki, Ernest Gellner, Feliks Koneczny and Andrzej Nowak). According to Znaniecki, a nation is a community based on commonly shared cultural convictions, and it has an objective status. Because of this, nation-building processes are not reducible to modernization or political processes, although the nation-state can be a result of nation-building processes. This approach allows us to conceptualize the peculiarities of the development of national consciousness in Central and Eastern Europe. In the final part of the paper, Znaniecki's vision of the world society based on national cultures is analysed. Celem artykułu jest interpretacja opracowanej przez Floriana Znanieckiego teorii narodu. Podstawą interpretacji będą następujące pytania/problemy badawcze: (1) Czy przynależność do narodu jest następstwem posiadania pewnych niezależnych od ludzkiej woli cech czy też rezultatem wolnego wyboru? (2) Czy procesy narodowotwórcze były autonomiczne wobec procesów społeczno-politycznych i społeczno-ekonomicznych, czy też były nich redukowalne? (3) Czy istniała (przynajmniej w Europie) jedna uniwersalna ścieżka procesów narodowotwórczych? Odpowiedź na tak postawione pytania pozwala umieścić poglądy Znanieckiego w szerszej perspektywie porównawczej i porównać jego ujęcie z ujęciami innych autorów (takich jak np. Zygmunt Balicki, Ernest Gellner, Feliks Koneczny czy Andrzej Nowak). Według Znanieckiego naród jest wspólnotą opartą na wspólnie podzielanych przekonaniach kulturowych, którym przyznawał obiektywny status. Z tego powodu procesy narodowotwórcze nie są redukowalne do procesów modernizacyjnych i politycznych, choć państwo narodowe może być następstwem procesów narodowotwórczych Takie ujęcie pozwala dostrzec specyfikę rozwoju świadomości narodowej w Europie Środkowej i Wschodniej. W końcowej części artykułu przedstawiam Znanieckiego wizję społeczeństwa światowego opartego na partykularnych kulturach narodowych.
The concept of the nation in the thought of Florian Znaniecki: an attempt of interpretation
Keywords: naród; Znaniecki; kultura; proces narodowotwórczy; świadomość narodowa; modernizacja; nation; nation-building process; nationalism; national elites; globalization